MARKETING MIX EFFECTS ON BEEF PURCHASE DECISIONS IN SUMEDANG - Ryan Feryana Kurniawan; Solihin Royani; Luthfianeu Febrianika (PT. Berkah Digital Teknologi, 2026)
Purpose: This study examines the effect of the perceived marketing mix on consumer purchase decisions at CV APN Mandiri Sumedang. Research Methodology: The study employed a quantitative, cross-sectional survey design. Data were collected from 70 customers using a structured questionnaire with a five-point Likert scale and a saturated sampling technique. Instrument quality was assessed using item–total correlation and Cronbach’s alpha. Data were analysed using descriptive statistics, the Shapiro–Wilk residual normality test, the Breusch–Pagan heteroscedasticity test, Pearson correlation, and simple linear regression with IBM SPSS Statistics version 26. Results: The marketing mix had a positive and significant effect on consumer purchase decisions (B=0.541, β=0.370, t=3.284, p=0.002). The model explained 13.7% of the variance in consumer purchase decisions (R2=0.137). The marketing-mix and purchase-decision indices were 80.03% and 78.23%, respectively. Limitations: The study was limited to 70 customers of one beef supplier, used a cross-sectional design and self-reported data, and examined the marketing mix as an aggregate construct. Contribution: The study provides empirical evidence for marketing management, consumer behaviour, food marketing, and local-enterprise management by explaining the relationship between integrated marketing activities and beef purchase decisions.